Far-field pattern formation by manipulating the topological charges of square-shaped optical vortex lattices - Stoyanov, Lyubomir; Maleshkov, G.; Zhekova, Maya; Stefanov, Ivan L; Neshev, D. N.; Paulus, Gerhard G.; Dreischuh, A. (Journal of the Optical Society of America B-Optical Physics, 2018)
In this work, we demonstrate experimentally the formation of 10 different structures consisting of bright beams with flat phase fronts in the focus of a lens (i.e., in the artificial far field). The basic structure used is a large, stable, square-shaped optical vortex (OV) array composed of vortices with alternating topological charges (TCs). The TCs of one individual OV, of a subarray of OVs, or of the complete OV lattice were erased/doubled in the cases of perfect superposition (on-site alignment) or are manipulated in phase in the cases of an offset between the vortices (off-site alignment). A dramatic reshaping of the beam is observed in the far field and shown to be in excellent agreement with numerical simulations.
CRIS-Team Scopus Importer:2023-04-20